1998
DOI: 10.1177/002215549804600105
|View full text |Cite
|
Sign up to set email alerts
|

Oncomodulin Is Expressed Exclusively by Outer Hair Cells in the Organ of Corti

Abstract: Oncomodulin (OM) is a small, acidic calcium-binding protein first discovered in a rat hepatoma and later found in placental cytotrophoblasts, the pre-implantation embryo, and in a wide variety of neoplastic tissues. OM was considered to be exclusively an oncofetal protein until its recent detection in extracts of the adult guinea pig's organ of Corti. Here we report that light and electron microscopic immunostaining of gerbil, rat, and mouse inner ears with a monoclonal antibody against recombinant rat OM loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 64 publications
5
76
1
Order By: Relevance
“…OM, the beta isoform of parvalbumin, discovered by MacManus (1979) and by Brewer and MacManus (1987) was known until now to be present in adult mammals only in the organ of Corti of the inner ear, in particular in the outer hair cells (Thalmann et al, 1995;Sakaguchi et al, 1998, Hackney et al, 2005. According to our present studies, an extensive system of OM-immunoreactive axons is present in the diencephalon of PV-deficient animals.…”
Section: Discussionsupporting
confidence: 64%
“…OM, the beta isoform of parvalbumin, discovered by MacManus (1979) and by Brewer and MacManus (1987) was known until now to be present in adult mammals only in the organ of Corti of the inner ear, in particular in the outer hair cells (Thalmann et al, 1995;Sakaguchi et al, 1998, Hackney et al, 2005. According to our present studies, an extensive system of OM-immunoreactive axons is present in the diencephalon of PV-deficient animals.…”
Section: Discussionsupporting
confidence: 64%
“…By first subdividing the organ of Corti into inner and outer layers, and ultimately into individual cell layers (Fig. 1C) we were able to localize oncomodulin expression exclusively to the outer hair cells later confirmed by immunohistochemistry [34]. Using the same techniques we were able to quantify the protein in the outer hair cells [35].…”
Section: Calcium-binding Proteinsmentioning
confidence: 87%
“…OM is present in the organ of Corti (Thalmann et al 1995), more precisely in cochlear outer hair cells (Sakaguchi et al 1998) in gerbil, rat, and mouse. An extracellular role for OM in retinal ganglion cell regeneration (Yin et al 2006) was reported, but see also Hauk et al (2008) and Schwaller (2009).…”
Section: Functional Aspects Of Parvalbumin and Oncomodulinmentioning
confidence: 99%